(untitled) (Journal of Universal Science Research, 2023)
This paper provides a critical review of the state of the art in code-switching research being conducted in linguistics. This study presents data on the discourse characteristics of code switching, and the functions that English has according to context. In addition, the data are described in relation to a language competence and preference. The study found that code switching occurred both within and across turns.